The United Kingdom's naval shipbuilding industrial base : the next fifteen years - Arena, Mark V.; Pung, Hans.; Cook, Cynthia R., 1965-; Marquis, Jefferson P.; Riposo, Jessie; Lee, Gordon T.; RAND Europe; International Security and Defense Policy Center; Rand Corporation. National Security Research Division; Rand Corporation; Great Britain. Ministry of Defence (Santa Monica, CA : RAND, 2005)
The United Kingdom has many contracted and prospective naval shipbuilding programmes on the horizon over the next two decades, ranging from the Astute-class attack submarine to the Future Aircraft Carrier (CVF). The UK Ministry of Defence (MOD) wants to know whether the United Kingdom's existing naval shipbuilding industrial base will be able to meet the requirements of the MOD's future acquisition plan. Using extensive surveys and a breadth of data, RAND researchers looked at the capacity of the UK naval shipbuilding industrial base and how alternative acquisition requirements, programmes, and schedules might affect this capability. Using the MOD's current plan, they focused on its potential impact in the areas of labour, facilities, and supplier demand. Overall, the researchers find that, using the 2004 planning assumptions, the overlap of certain large programmes would cause a near-term peak in workload demand, followed by a steady decline. To minimise such inconsistencies, they suggest that the MOD in the near term consider, among other options, shifting the scheduling of the labour demand (known as "level-loading"); reexamining the current UK Defence Industrial Policy to allow non-UK firms to meet peak demand; and using alternative facilities to assist major construction during peak workload times. For the long term, the researchers recommend, among other alternatives, that the MOD make long-term industrial planning outlooks of this report's nature a regular occurrence, define an appropriate role for the United Kingdom's supporting offshore industry, and explore the advantages of interoperable technologies for sharing design work.
Introduction -- Labour Demand -- The Supply of Naval Shipyard Labour in the United Kingdom -- Facilities Utilisation at the UK Shipyards -- The UK Shipbuilding Supplier Industrial Base -- Nontraditional Sources for Naval Shipbuilding: Commercial Shipbuilding and Offshore Industries -- Issues for the Ministry of Defence to Consider.
"RAND Europe."
Includes bibliographical references (p. 175-178).
Also available on the internet via WWW in PDF format.
Keywords: Great Britain. -- Ministry of Defence -- Procurement; Great Britain. -- Royal Navy -- Procurement; Navy-yards and naval stations -- Great Britain; Shipbuilding industry -- Great Britain; Warships -- Great Britain -- Design and construction